2017
DOI: 10.2147/opth.s141255
|View full text |Cite
|
Sign up to set email alerts
|

A novel nomogram for the treatment of astigmatism with femtosecond-laser arcuate incisions at the time of cataract surgery

Abstract: PurposeThe purpose of this study was to determine an arcuate incision (AI) nomogram to treat astigmatism during femtosecond laser-assisted cataract surgery.MethodsThis is a retrospective, cohort study. Femtosecond laser (FSL)-assisted transepithelial AIs were created at a 9.0 mm optical zone, 80% depth, centered on the limbus. We modified the manual Donnenfeld limbal relaxing incision nomogram to 70% for with-the-rule (WTR), 80% for oblique (OBL), and 100% for against-the-rule (ATR) astigmatism. The correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…Of the few studies that have investigated femtosecond laser AK or LRI efficacy, all reported their nomograms undercorrected. 7,20,21 Both Baharozian et al's anterior penetrating transepithelial LRIs and Day et al's paired intrastromal AKs significantly reduced corneal astigmatism, although their nomograms systematically undercorrected. 7,20 In Day et al's study, however, this was the intended outcome as they aimed to provide 70% astigmatism magnitude correction in order to avoid overcorrections.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Of the few studies that have investigated femtosecond laser AK or LRI efficacy, all reported their nomograms undercorrected. 7,20,21 Both Baharozian et al's anterior penetrating transepithelial LRIs and Day et al's paired intrastromal AKs significantly reduced corneal astigmatism, although their nomograms systematically undercorrected. 7,20 In Day et al's study, however, this was the intended outcome as they aimed to provide 70% astigmatism magnitude correction in order to avoid overcorrections.…”
Section: Discussionmentioning
confidence: 98%
“…7,20,21 Both Baharozian et al's anterior penetrating transepithelial LRIs and Day et al's paired intrastromal AKs significantly reduced corneal astigmatism, although their nomograms systematically undercorrected. 7,20 In Day et al's study, however, this was the intended outcome as they aimed to provide 70% astigmatism magnitude correction in order to avoid overcorrections. 7 Chan et al also found their personal nomogram of single, non-paired, femtosecond anterior penetrating AKs undercorrected overall, but overcorrections were seen when preoperative astigmatism <1.0D 21 a finding similar to the current study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently published nomograms for both transepithelial and intrastromal arcuate incisions provide a useful starting point. 17 19 However, additional data and refinement of nomograms will improve predictability and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This technique obviates the insertion of a toric lens and can thus be considered a safer and more economical means for the correction of low-tomoderate corneal astigmatism. 15 The proximity of the Femto LDV Z8 to the patient's bed allowed us to employ a double-docking technique and conduct the procedure of FSAK and CCI separately from CCC and lens fragmentation. This two-step procedure, without any patient transfer, maximizes the benefits of FLACS.…”
Section: Introductionmentioning
confidence: 99%